2019
DOI: 10.26656/fr.2017.4(1).155
|View full text |Cite
|
Sign up to set email alerts
|

A review on Listeria monocytogenes in food: prevalence, pathogenicity, survivability and antibiotic resistance

Abstract: The ubiquitous of Listeria monocytogenes in the environment and in the niche of foods can be related with the ability of the pathogen to survive in adverse conditions, in example, low temperature and pH, high concentrations of salt and bile, oxidative stress and carbon starvation. Besides, most of the human listeriosis are food-borne and L. monocytogenes consists of a spectrum of strains with varying virulence and pathogenicity. Moreover, the virulent regulators play a role in facilitating better adaption or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…It has been indicated that listeriosis carries high rates of hospitalization and mortality. Nearly 94% of confirmed cases of listeriosis need to be hospitalized, and 14% of them die (9,39). Based on the somatic O antigen, L. monocytogenes can be subclassified into 13 serotypes.…”
Section: Monocytogenes In Meat and Meat Productsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been indicated that listeriosis carries high rates of hospitalization and mortality. Nearly 94% of confirmed cases of listeriosis need to be hospitalized, and 14% of them die (9,39). Based on the somatic O antigen, L. monocytogenes can be subclassified into 13 serotypes.…”
Section: Monocytogenes In Meat and Meat Productsmentioning
confidence: 99%
“…All the 13 serotypes can cause listeriosis; however, serotypes 1.2b, 1.2a, and 4b are more widespread (27,40). Apart from food matrix diversity, capacity for pathogenicity, and geographical area, the most isolated serotypes from food products are 4c, 4b, 3b, 1.2a, and 1.2b (9,41).…”
Section: Monocytogenes In Meat and Meat Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…pathogens from various sources, food processing as well as consumption. Salmonella spp., Listeria monocytogenes are the most frequently potential pathogens associated with milk and dairy products 10 . Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%